Culture and society, 1780-1950 - Williams, Raymond (Middlesex, 1985)
In Culture and Society Raymond Williams has traced the idea of culture as it has developed in Britain from 1780 to 1950, 'culture' being defined as 'right knowing and right doing' and considered throughout in its relation to society rather than in its purely artistic sense. With its learning, good sense, independence of mind, and its refusal to despair of modern civilization - above all in its insistence on the living relationships between artistic and social development - Culture and Society is proving to be one of the seminal works of our time.
Keywords: Society